IDEIS: a tool to identify PTPRC/CD45 isoforms from single-cell transcriptomic data - Michalik, Juraj; Niederlova, Veronika; Stepanek, Ondrej (Frontiers in Immunology, 2024)
Single-cell RNA sequencing (scRNAseq) methods are widely used in life sciences, including immunology. Typical scRNAseq analysis pipelines quantify the abundance of particular transcripts, without accounting for alternative splicing. However, a well-established pan-leucocyte surface marker CD45, encoded by the PTPRC gene, presents alternatively spliced variants that define different immune cell subsets. The information about some of the splicing patterns in particular cells in the scRNAseq data can be obtained using isotype-specific DNA oligo-tagged anti-CD45 antibodies. However, this requires generation of an additional sequencing DNA library.Here, we present IDEIS, an easy-to-use software for CD45 isoform quantification, which uses single-cell transcriptomic data as the input. We show that IDEIS accurately identifies canonical human CD45 isoforms in data sets generated by 10X Genomics 5' sequencing assays. Moreover, we used IDEIS to reveal the specificity of Ptprc splicing pattern for mouse leukocyte subsets.